Taxi audio resource to strengthen listening skills to drivers of cooperativa Brisa Azul, Salinas, Santa Elena province, 2015. - González Baldeón, Juan Carlos (2016)
This research was aimed at taxi drivers of cooperativa Brisa Azul in order to improve their listening skills and learn basic expressions in english to provide a better service to tourists visiting santa elena province. the study analyzes the reasons why taxi drivers have difficulties with the listening skill in the English language, the results permitted to create a resource with audios to strengthen listening on drivers, the exploratory research using qualitative methods and techniques of observation allowed to create a solution for the problem. After leaving the airport, taxi drivers are the next people that tourists meet in order to take them to the hotel. english for taxi drivers is an educational option for drivers of cooperativa Brisa Azul in Salinas, Santa Elena province to enhance their listening skill in english with the tool of an audio cd and a web page, to train cab drivers at least with expressions to provide passengers a better service. This material has listening exercises with common phrases used in their professional activity, repeating and listening phrases with specific vocabulary to understand english in the workplace itself.